Rising unemployment in Argentina: 1974 - 1993 - Giacchino, Leonardo (1994)
This paper presents evidence on the evolution of unemployment in Argentina for the period 1974-1993. Argentina has been traditionally a country with relatively low unemployment rates; although the fear of increasing rates of joblessness has been in the mind of government and politicians for very long. This article studies the determinants of both secular and cyclical increase in unemployment in Argentina since 1974. The first objective is to document the "stylized facts" about unemployment during this period. Much of the work of this paper has been to gather almost in an economic history fashion data that was scattered, almost never used seriously, hidden by government officials and never interpreted before. The second objective is to establish the importance of available theories of unemployment on the light of the Argentine evidence. It does not provide complete answers to the reasons for the increase in unemployment but it does identify avenues for further research.